Getting a foot in the door. Spaces of cocaine trafficking in the Port of Rotterdam - Roks, Robby (Trends in organized crime, 2021)
As an important gateway to Europe, the Port of Rotterdam is known for its high-quality facilities and efficiency, but also attracts organised crime groups who use the transatlantic legal trade flows to traffic cocaine. Based on a qualitative study, consisting of 73 interviews with public and private actors, an analysis of 10 criminal investigations and field visits to public and private organisations in the port, this article examines how organised crime groups involved in cocaine trafficking take advantage of or adapt to the socio-spatial relations in the Port of Rotterdam. First, we pay attention to which physical spaces in the port of Rotterdam provide opportunities for cocaine trafficking. Second, we examine how the occupational and legal environment in which people, private companies and law enforcement agencies in the port work and interact provide opportunities for cocaine trafficking. Our findings demonstrate that increased security measures by both public and private actors directed at physical spaces result in a displacement to new spaces in and around the port of Rotterdam. Furthermore, the current socio-spatial relations in the port of Rotterdam also make the role of people on the inside – referring to a whole range of public and private employees – increasingly indispensable.